The Risk of Nephrolithiasis Among Patients With Ankylosing Spondylitis: a Population-Based Cohort Study - Mu Tsun SHIH; Shou Hung TANG; Tai Lung CHA; Sheng Tang WU; Jen Huai CHIANG; Wen Chi CHEN (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the correlation of ankylosing spondylitis (AS) with nephrolithiasis by performing a nationwide population- based cohort study. Patients and methods: The data used in this retrospective cohort study were collected from the Taiwan National Health Insurance Research database. The study included a total of 3,334 AS patients (1,914 males, 1,420 females; mean age 44.51±16.83 years; range 22 to 79 years) and 13,336 non-AS patients (7,656 males, 5,680 females; mean age 44.27±17.01 years; range 21 to 78 years) who had been followed-up on an average of 6.78 years and 6.75 years, respectively, between January 2000 and December 2008. Results: The percentage of newly diagnosed nephrolithiasis was 4.8% in all study subjects. However, the percentages of newly diagnosed nephrolithiasis were 5.76% and 4.58% in the AS and non-AS cohorts, respectively. After adjusting the patients’ sex, age, urbanization level, and comorbidities, the hazard ratio obtained from our multivariable Cox model was 1.19. Conclusion: Our study findings indicate that patients with AS are more likely to develop nephrolithiasis than non-AS patients.